Obtaining More Realistic Cross-Layer QoS Measurements: A VoIP over LTE Use Case - Rivas Tocado, F. Javier; Díaz-Zayas, Almudena; Merino-Gómez, Pedro (Wiley, 2013)
We introduce a real-time experimentation testbed in this paper which enables more realistic analysis of quality of service (QoS) in LTE networks. This testbed is envisioned for the improvement of QoS and quality of experience (QoE) through the experimentation with real devices, services, and radio configurations. Radio configurations suggested in the literature typically arise from simulations; the testbed provides a real and controlled testing environment where such configurations can be validated. The added value of this testbed goes a long way not only in the provision of more realistic results but also in the provision of QoS and QoE cross-layer measurements through the correlation of information collected at different layers: from service and IP levels to radio and protocol parameters. Analyzing the interlayer dependencies will allow us to identify optimal settings for the radio access network and service parameters. This information can be used to suggest new cross-layer optimizations to further improve quality of experience of mobile subscribers. As a use case, we examine VoIP service over LTE, which is currently an open issue.
Keywords: Redes de ordenadores; Control de calidad; Performance; Quality of Service; VoIP; Mobile networks